Perspectives on the Success and Early History of the Industrial Institute for Economic and Social Research (IUI) - Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2009)
The Industrial Institute of Economic and Social Research (IUI) was founded in 1939. In less than ten years, IUI grew from a small survey bureau to a leading research institute focused on microeconomic research relevant to industrial development. Based on a number of new commemorative essays and biographies written by or about former IUI researchers published in Henrekson (2009), this essay describes the Institutes accomplishments and the particular research environment at IUI. It also discusses the conditions conducive to a creative, productive research environment. While most of these accounts do not extend beyond the end of the 1970s, the insights provided are highly relevant for contemporary research institutes.
Keywords: B31; D02; D21; L20; O14; 330; Applied research; Creativity; Entrepreneurship; Research institute; Wirtschaftsforschung; Entrepreneurship-Ansatz; Wirtschaftsforschungsinstitut; Schweden